2018
DOI: 10.3855/jidc.10328
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of Staphylococcus aureus associated with nasal colonization among healthcare workers using DNA microarray

Abstract: Introduction: Healthcare workers (HCWs) colonized with Staphylococcus aureus may serve as a reservoir of infection. This study was carried to determine the genetic make-up of S. aureus nasal colonizers in HCWs. Methodology: Nasal swabs were obtained from 93 HCWs and molecular characterization of identified S. aureus isolates was carried out using the StaphyType DNA microarray (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…We had previously reported CC1153-MSSA as nasal colonizer in health care workers at KKUH but this is the first identification of CC1153-MRSA in this facility 9. In our region, the two CC1153-MRSA isolates reported have been from Kuwait 5,20.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…We had previously reported CC1153-MSSA as nasal colonizer in health care workers at KKUH but this is the first identification of CC1153-MRSA in this facility 9. In our region, the two CC1153-MRSA isolates reported have been from Kuwait 5,20.…”
Section: Discussionmentioning
confidence: 71%
“…Recently reported work showed the presence of a high degree of diversity and an emergence of both pandemic and rare MRSA strains among isolates obtained from 2009 to 2015 at King Khaled University Hospital (KKUH), Riyadh, Saudi Arabia 8. Further work also showed that MRSA colonizing health care workers at the facility were of similar population structure as those identified in patients 9…”
Section: Introductionmentioning
confidence: 96%
“…In the UAE, novel variants of this MRSA strain and putative PVL-deletion mutants have been reported ( Senok et al., 2020a ). For CC15-MRSA-[V+ fusC ] the ancestral CC15-MSSA is a common nasal colonizer in the Middle East ( Sarkar et al., 2016 ; Senok et al., 2018 ). However, in recent years, CC15-MRSA has emerged among humans and livestock (camels) in the UAE, Kuwait and Saudi Arabia ( Raji et al., 2016 ; Senok et al., 2017 ; Boswihi et al., 2018 ; Senok et al., 2020a ).…”
Section: Discussionmentioning
confidence: 99%
“…(23.5%)[44,50,106,109,111,115,127,129,143,160,170,174] (29.4%)[50,53,54,61,63,64,73,85,101,102,118,126,131,132,147] …”
mentioning
confidence: 99%